SOFT GROUPOID AND ITS PROPERTIES - Abdurrahman, Saman (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN (EPSILON: JOURNAL OF PURE AND APPLIED MATHEMATICS), 2024)
A groupoid is a generalized form of the concept of a group, achieved by omitting the properties of associativity, identity, and inverses. In this paper, we introduce the concept of a soft groupoid, which serves as a generalization of the soft group. We define and explore the properties of intersection, AND, and union on soft groupoids and soft subgroupoids. Furthermore, we explore the properties of these operations when applied to collections of soft subgroupoids derived from a given soft subgroupoid.